Hubungan Pengetahuan dan Sikap terhadap Kejadian Anemia pada Remaja Putri di SMK PGRI 2 Kota Jambi - Haryanti, Dwi; Putri, Aninda Ayu; Susanti, Desy; Desilawati, Fitria (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the relationship between knowledge and attitudes towards the incidence of anemia in young women at SMK PGRI 2 Jambi City. This research is a quantitative study with a retrospective approach. The population in this study were young women at SMK PGRI 2 Jambi City in 2024 totaling 201 female students and a sample of 67 female students. The data collection technique used random sampling with data analysis using the chi-square test. The results of the study showed that there was no relationship between adolescent knowledge and attitudes and the incidence of anemia in adolescent girls at SMK PGRI 2 Jambi City.